A new anastomosis technique for intestinal diseases with proximal dilated segments - Metin Gündüz (Wolters Kluwer Medknow Publications, 2016)
A number of techniques have been described for intestinal anastomosis. We describe a different, simple, and safe technique that can be used in patients with intestinal diseases, such as jejunoileal atresia and perforation that has proximal dilated segments. In this technique, an atraumatic bowel clamp was applied on the proximal dilated bowel at a 90° angle. In the narrow distal segment, we resected the bowel at a 0° angle and continued at a 30° angle from the antimesenteric side. Finally, a two-layer interrupted anastomosis was performed. We applied this technique to a 31-day-old patient who had a divided jejunostomy due to malrotation and perforation with a proximal dilated bowel. Neither anastomotic complications nor feeding and passage problems were seen postoperatively.